Is small beautiful? Is big efficient? Selected patterns of HRM: A pilot study of two Russian companies - Julia Rozanova (Journal for East European Management Studies, 2002)
The article focuses on patterns and strategies developed by particular business enterprises that help to cope with the challenges of transition, like changes of property ownership, companies' structure, principles of performance, and patterns of business-government relations. The paper is based on several casestudies: those of the biggest and most influential Russian corporations (LUKOIL, GAZPROM and ROSTELECOM), and those of small business firms (a factory; an equipment-sales middleman). The author analyses the systems of industrial relations and measures of personnel adjustment to the challenges of transition developed by the selected Russian companies in comparison to how these measures are perceived, evaluated and consequently responded to by employees. The patterns applied by big corporations (Blue Chips) and small companies differ considerably. The size of a company is a crucial factor here, as well as the history of a company's transformation, and the personalities of the company's leaders and their participation and role in the political process. – – Der Artikel konzentriert sich auf Muster und Strategien von Unternehmen zur Begegnung der Herausforderungen des Überganges wie der Änderung des Eigentumrechtes, der Unternehmensstruktur, Leistungsprinzipien und Beziehungsmuster zwischen Regierung und Unternehmen. Er basiert auf mehreren Fallstudien in einigen der größten und einflussreichsten russischen Unternehmen (LUKOIL, GAZPROM und ROSTELECOM) sowie kleinen Unternehmen (eine Fabrik, ein Kaufmann). Der Artikel analysiert die Systeme der industriellen Beziehungen und Maßstäbe der personellen Eignung für den Übergang, die von ausgewählten russischen Firmen entwickelt wurden, und inwiefern diese Maßstäbe anerkannt, bewertet und folglich von den Angestellten erwidert wurden. Die Muster die von den großen Konzernen (Blue Chips) und kleinen Firmen eingesetzt wurden, unterscheiden sich dabei erheblich.
Keywords: 650